Digitalization in management accounting systems for urban SMEs in a developing country: A mediation model analysis - Dwi Ratmono; Frendy; Zuhrohtun Zuhrohtun (Cogent Economics & Finance, 2023)
This study aims to examine the role of digitalization in management accounting systems (DIMAS) in increasing the effectiveness of management decision-making in urban small and medium enterprises (SMEs) in a developing economy. This study also investigates the mediating role of information quality (accuracy and timeliness) and cost reduction in the relationship between DIMAS and management decision-making. This research employed primary data collected from questionnaire responses from 536 urban SMEs that implemented digitalization in a developing economy setting. The results show that DIMAS has a positive effect on the accuracy and timeliness of accounting information and cost reduction, which in turn contribute to better decision-making. The results of the mediation test reveal that the accuracy and timeliness of accounting information and cost reduction mediate the relationship between DIMAS and management decision-making. The findings of this study provide empirical evidence on the importance of digitalization for urban SMEs operating in a developing country, enabling them to survive and achieve a competitive advantage in an era of high uncertainty due to the industry 4.0 and the COVID-19 pandemic.
Keywords: 330; accuracy and timeliness; cost reduction; decision-making; digitalization; management accounting system